PENGARUH MOTIVASI, DISIPLIN DAN KEPUASAN KERJA TERHADAP KINERJA ANGGOTA TNI DI MARKAS ZIDAM XII/TANJUNGPURA KABUPATEN KUBU RAYA - B31110060, Rafika Olliza (Jurnal Manajemen Update, 2016)
Zeni Headquarters Military Region XII / TPR Kubu Raya (abbreviated Mazidam XII / Tanjungpura) is one of the implementing agencies of activities at the military command XII / Tanjungpura, whose principal duty to foster and perform the functions of Zeni and Nubika Army. In the human resources aspects of Zeni Headquarters Military Region XII / TPR has been implementing various policies in terms of increasing work motivation, discipline and strive to provide job satisfaction to its members in order to increase their performance. The purpose of this study was to examine and analyze the influence of motivation on the performance of members of the TNI Headquarters Zidam XII / Tanjungpura District Kubu Raya and to test and analyze the effect of labor discipline on the performance of members of the TNI Headquarters Zidam XII / Tanjungpura District Kubu Raya as well as to test and analyze the influence job satisfaction on the performance of members of the TNI Headquarters Zidam XII / Tanjungpura Kubu Raya. This research method is associative. Data collection techniques: interviews, questionnaires and documentary studies. The population in this study is the population in this study were all soldiers in the Headquarters Zidam XII / Tanjungpura District Kubu Raya total of 65 people in 2015. So samples taken are all soldiers TNI Headquarters Zidam XII / Tanjungpura District Kubu Raya numbering totaling 65 people in 2015, while the method used for sampling the census technique and analyzed quantitatively. The results of the study as follows: There was a significant effect of motivation on the performance of members of the TNI Headquarters Zidam XII / Tanjungpura Kubu Raya. There was a significant influence on the performance of labor discipline members of the TNI Headquarters Zidam XII / Tanjungpura District Kubu Raya and no significant effect of job satisfaction on the performance of members of the TNI Headquarters Zidam XII / Tanjungpura Kubu Raya. Keywords: Motivation, Discipline Work, Job Satisfaction and Performance